دور جودة الخدمات السياحية في تحقيق رضا العملاء دراسة حالة عينة من الوكالات السياحية الأغواط - معاش أسامة; بن عبد الرحمان محمد; بن قشوة جلول (جامعة عمار ثليجي الاغواط, 2022)
This study aims to identify the impact of the quality of tourism services in achieving customer satisfaction among a sample of clients of tourism agencies in the state of Laghouat. The study sample included (60) clients, and this effect was tested using multiple regression analysis. The results indicated that there was a statistically significant effect between the two variables of the study (the quality of tourism services and customer satisfaction), and the study concluded several results, the most important of which are: - Service quality is an important source of maintaining existing clients for tourism agencies in addition to attracting new clients. Satisfaction is a psychological state or emotional feeling experienced by the client as a result of comparing the performance of services and expectations, which means that satisfaction is related to the level of perceived service quality and that the degree Satisfaction determines the level of satisfaction; - Service quality standards enable the customer to evaluate the quality level of any service institution.